Flexibility in management of modernization in construction - electrical works = Elastyczność w zarządzaniu modernizacją obiektów budowlanych na przykładzie robót elektrycznych - Nowotarski, Piotr; Pasławski, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the general principles of flexible approach, illustrated with case study regarding flexibility in modernization. Flexibility is understood in the present case as a skilful adaptation to changes in the dynamically changing environment. The essence of flexibility approach is being staged to make decisions based on environmental and process monitoring in progress.
Keywords: obiekty budowlane; modernizacja oświetlenia; technologia LED; oszczędności energii; flexible approach; light modernization; electrical contractor; energy savings modernization